Correlations between Ape1/Ref-1, ICAM-1 and IL-17A Levels in Serum and Radiation Pneumonitis for Local Advanced Non-small Cell Lung Cancer Patients - Leiming GUO; Gaofeng DING; Wencai XU; Hong GE; Yue JIANG; Yufei LU (Chinese Journal of Lung Cancer, 2018)
Background and objective The main manifestations of radiation pneumonitis are injury of alveolar epithelial and endothelial cells, abnormal expression of cytokines, abnormal proliferation of fibroblasts and synthesis of fibrous matrix. The occurrence of radiation pneumonitis is associated with multiplecytokine level abnormality. These cytokines can also be used as bio-markers to predict the occurrence of radiation pneumonitis. This study was to evaluate the correlation between the change of apurinic/apyrimidinic endonuclease 1/redox factor-1 (Ape1/Ref-1), intercellular adhesion molecules 1 (ICAM-1) and interleukin-17A (IL-17A) before and after radiotherapy and radiation pneumonitis for local advanced non-small cell lung cancer (NSCLC) patients with concurrent chemoradiotherapy. Methods NSCLC patients (68 cases) were treated with concurrent radiotherapy and chemotherapy, every patient’s normal tissue were controlled with a same radation dose. 68 local advanced NSCLC patients with concurrent chemoradiotherapy were detected the levels of Ape1/Ref-1, ICAM-1 and IL-17A in serum by ELISA before radiotherapy and in the 14th week after radiotherapy. Acute and advanced radiation pulmonary injury was graded according to Radiation Therapy Oncology Group/European Organization For Research and Treatment (RTOG/EORTC) diagnostic and grading criteria. Grade 2 or more radiation pneumonitis was taken as the main end point. Results Eighteen cases out of 68 developed radiation pneumonitis, 50 of 68 cases have no radiation pneumonia development. There was no significant change of Ape1/Ref-1 levels before and after radiotherapy in radiation pneumonitis group (P>0.05). There was no significant change of Ape1/Ref-1 concentration in serum after radiotherapy between radiation pneumonitis group and non-radiation pneumonitis group (P>0.05). Compared with before radiotherapy, upregulation degree of ICAM-1 levels in radiation pneumonitis group was significantly higher than that in non- radiation pneumonitis group (P<0.05). There was no significant change of IL-17A concentration before and after radiotherapy in radiation pneumonitis group, but after radiotherapy IL-17A concentration in serum were remarkably higher than that in non-radiation pneumonitis group (P<0.05). Correlation analysis found that the change of ICAM-1 before and after radiotherapy has no obvious correlation with the incidence of radiation pneumonitis, and IL-17A change has obvious correlation with the incidence of radiation pneumonitis. Conclusion On the basis of strictly controlling radiation dose on normal tissue, IL-17A in serum could be the predictive factors of radiation pneumonitis for local advanced NSCLC patients with concurrent chemoradiotherapy.